The effectiveness of dry needling for plantar fasciitis: a systematic review and meta-analysis - Yang, Aiguo; Lin, Rong; Xia, Mingwei; Su, Hao; He, Ying (Frontiers in neurology, 2024)
To evaluate the effectiveness of dry needling (DN) on pain and functional outcomes in patients with plantar fasciitis (PF). PubMed, Embase, the Cochrane Library, EBSCO, web of science, physiotherapy Evidence Database (PEDro) were searched for randomized control trials (RCTs) evaluating the effectiveness of dry needling on plantar fasciitis. Article screening, data extraction and risk-of-bias evaluation were independently performed by two reviewers. Meta-analysis was conducted based on different control methods and assessment time using RevMan 5.3 software. A total of 12 RCTs involving 781 patients were included in the systemic review and meta-analysis. The comparison of DN + routine treatments vs. routine treatments alone demonstrated that PF patients receiving DN have significantly lower scores in Visual Analog Scale / Numerical Pain Rating Scale (VAS/NPRS) [95%CI (-2.12, -1.76), < 0.0001], and the scores of Foot Function Index (FFI) [95%CI (-12.57, -3.58), = 0.004]. In the comparison of DN vs. other treatments, results showed that DN significantly lowered the scores of FFI [95%CI (-6.55, -1.09), = 0.006]. However, there was no significant difference in pain improvement between DN and other treatments [95%CI (-0.66, 0.06), = 0.10]. In the meta-analysis based on different assessment time, results showed that there was significant difference in the scores of VAS/NPRS within 1 month, at 1 month and at over 1 month. But there was no significant difference in the scores of FFI within 1 month, while at 1 month and at over 1 month, the scores of FFI were lowered in patients receiving DN, and the difference were statistically significant. Dry needling is effective in relieving pain and restoring function in patients with plantar fasciitis. Furthermore, dry needling may take at least 1 month to take effects in patients with plantar fasciitis. More multi-center RCTs with high-quality, large sample size are needed to further conform our conclusion.